Amplified effect of surface charge on cell adhesion by nanostructures. Issue 25 (6th May 2016) - Xu, Li-Ping; Meng, Jingxin; Zhang, Shuaitao; Ma, Xinlei; Wang, Shutao
Abstract : The effect of surface charge on cell adhesion can be significantly amplified by integrating nanostructures, as revealed by cell adhesion performance, cell morphology and corresponding cytoskeletal organization. Abstract : Nano-biointerfaces with varied surface charge can be readily fabricated by integrating a template-based process with maleimide–thiol coupling chemistry. Significantly, nanostructures are employed for amplifying the effect of surface charge on cell adhesion, as revealed by the cell-adhesion performance, cell morphology and corresponding cytoskeletal organization. This study may provide a promising strategy for developing new biomedical materials with tailored cell adhesion for tissue implantation and regeneration.